Web-Based Sales Management Information System for PT Sinarta Karya Papua Using Rapid Application Development - Haloho, Haloho; Kiswanto, Rahmat Haryadi; Lahallo, Jim; Haloho, Jayando (LPPM Universitas Sains dan Teknologi Komputer, 2025)
PT. Sinarta Karya Papua, a medium-scale enterprise in Eastern Indonesia, faces operational challenges due to its reliance on manual sales recording systems, leading to data duplication, delayed reporting, and limited information transparency. This hinders operational efficiency and strategic decision-making. This study aims to develop a web-based sales management information system addressing these issues using the Rapid Application Development (RAD) methodology, selected for its rapid prototyping and iterative adaptation to user needs. Data was gathered through field observations, semi-structured interviews with staff and management, and literature reviews on information systems and RAD. The system was developed with PHP and MySQL to ensure flexibility and reliable data management. Findings demonstrate the successful integration of sales transaction processing, customer management, inventory control, and real-time reporting modules. Comprehensive functional testing (Blackbox Testing) confirmed 100% operational accuracy across all features, significantly improving record-keeping efficiency and information accessibility. The primary contribution lies in implementing RAD within Papua's unique business context—an underexplored area in existing literature. The system delivers a practical solution for PT. Sinarta Karya Papua while serving as a reference model for similar enterprises in geographically challenging regions. Key implications include enhanced organizational competitiveness through digital transformation and the potential replication of this framework across other business sectors in Eastern Indonesia.